(untitled) (Fiep Bulletin - online, 2014)
this study addresses the benefits, education, and professional intervention adaptations for disabled swimming. This study aimed to describe the benefits of swimming learning for the visually impaired. The type of study was expository review using a strategy of seeking original articles, review articles, monographs, dissertations, theses and laws in the electronic databases of Google Scholar, Scientific Electronic Library Online (SciELO), Planalto.gov data and anal event of Brazilian universities , addressing methods and adaptations of teaching . After analysis and synthesis of research, it is concluded that the practice of swimming for the visually impaired person promotes stimuli necessary for development: the functional capacity of the physical, social and emotional aspects. Improving self-esteem and quality of life of the individual causing him to accept the disability and promote independence both in the aquatic and terrestrial environment.